An instrument for measuring scientific empathy in students’ disciplinary engagement: the scientific empathy index - Yang, Heesun; Anderson, David; Kang, Seong-Joo (Frontiers in Education, 2023)
A crucial component to disciplinary engagement for learners in science is that of scientific empathy in other words, the metaphysical connection between the student and the object of study as scientists do when deeply engaged in their work. Scientific empathy is the factor that stimulates and maintains students' desire to inquire and that elicits creative problem-solving in their "doing" science as a distinctive disposition from general empathy. As such, in this study, the scientific empathy index (SEI) was developed to measure these traits of scientific empathy. For this purpose, two-rounds of factor analyses were conducted in the preliminary and the main tests of SEI. For proving the validity of the main test, correlation and mediated analysis were additionally conducted between other problem-solving scales and Final SEI. The first-factor analysis was conducted on 1,048 elementary, middle and high school students as a preliminary test for extracting SEI questions. Based on the preliminary test results, 956 K-12 students were newly recruited, and the validity of the main test was confirmed through a second-factor analysis. Through these analyses, it was identified that the scale comprised five factors: sensitivity, situational interest, scientific imagination, empathetic concern, and empathetic understanding of others. Each scientific empathy factor revealed both cognitive and affective process dimensions including individual and social interrelations of students' empathy in doing science. SEI was more highly correlated than the general empathy scale in the process of creative problem-solving and science process skills. In addition, it was found to exhibit a mediating effect between creative problem-solving and scientific inquiry. These findings validate the newly developed SEI and how it contributes to providing science learners with a useful tool for quick and easy measurement of scientific empathy and its components for the empathized involvement process between the student and their research subject.